Silver Stars Enters Sixth Decade - Unknown (Newsday)
This article discusses the Silver Stars Steel Orchestra’s 60th anniversary plans. Mr Keith Byer, the band's Manager gave an overview of the plans.
Keywords: Steel bands (Music) -- Development -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago